O ensino de Física e os museus de ciência - Souza, César Augusto Morais de [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Based on the ideas of Gaspar and Marandino, discuss the teaching of physics through Museums and Science Centers, drawing on ideas such as: Scientific Literacy, Informal Education and Zone of Proximal Development. We visited and analyzed the museums: Museum of Energy Rio Claro - Mill Park Corumbataí, Catavento Culture and Education - Social Organization of Culture, Centre for Scientific and Cultural (CDCC) and Studies Center of the Universe - CEU. Point out elements of these museums that benefit the formal teaching of physics in schools, as well as positive elements of schooling that maximize the experience of museum visits

Baseados nas idéias de Gaspar e Marandino, discutiremos o ensino de física por meio de Museus e Centros de Ciências, valendo-se de idéias tais como: Alfabetização Científica, Ensino Informal e Zona de Desenvolvimento Proximal. Visitamos e analisamos os museus: Museu da Energia de Rio Claro – Usina Parque do Corumbataí, Catavento Cultura e Educacional – Organização Social de Cultura, Centro de Divulgação Científica e Cultural (CDCC) e Centro de Estudos do Universo - CEU. Apontaremos elementos desses museus que beneficiam o ensino formal de física em escolas, assim como elementos positivos do ensino escolar que maximizam a experiência de visitas aos museus
Keywords: Física - Estudo e ensino; Museus de ciencia; Divulgação científica